Level of Pain and Physical Function in Patient with Chronic Knee Pain Visiting Dhulikhel Hospital - Kandel, B.; Badal, S. (Kathmandu University Medical Journal, 2021)
Background Chronic knee pain is a common and major health problem in ageing population which is also associated with high levels of disability. So early detection and treatment of pain related functional limitation is likely to have major influence on healthy ageing. Objective To quantify the level of pain and physical function in patient with chronic knee pain. Method Preliminary screening of population with chronic knee pain was taken and cross sectional descriptive study was done. Questionnaire with inclusion criteria was fulfilled with administration of Nepali version of Numerical Pain Rating Scale and Nepali version of Patient Specific Functional Scale on interview as well as self-report basis. Data was collected, recorded and analyzed using Statistical Package for the Social Sciences (SPSS) version 23. Result Chronic knee pain was found in 75.6% of female with the average pain level found to be 5 in Nepali version of Numerical pain rating scale. Sitting function was found to be affected in 82.1% of population with mean score of 2 in Nepali version of Patient specific functional Scale. Similarly 80.8% reported going downstairs to be difficult due to knee pain. Conclusion Pain and functional disability are the principle findings in patient with chronic knee pain for which they seek medical treatment. So the treatments should target on functional task with effective strategy to address disability. Focus on function is important for the development of optimal rehabilitation programs in patients with chronic knee pain.